2011
DOI: 10.1021/bi2009135
|View full text |Cite
|
Sign up to set email alerts
|

A Protein Engineering Approach Differentiates the Functional Importance of Carbohydrate Moieties of Interleukin-5 Receptor α

Abstract: Human interleukin-5 receptor α (IL5Rα) is a glycoprotein that contains four N-glycosylation sites in the extracellular region. Previously, we found that enzymatic deglycosylation of IL5Rα resulted in complete loss of IL5 binding. To localize the functionally important carbohydrate moieties, we employed site-directed mutagenesis at the N-glycosylation sites (Asn(15), Asn(111), Asn(196), and Asn(224)). Because Asn-to-Gln mutagenesis caused a significant loss of structural integrity, we used diverse mutations to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Furthermore, we have recently shown that N-glycosylation of the IL-6 receptor (IL-6R) is dispensable for its biological function, but rather influences limited proteolysis of the IL-6R by the metalloprotease ADAM17 [25]. In contrast, the receptors for C-X-C motif chemokine 12 (CXCL12), granulocyte-macrophage colony-stimulating factor (GM-CSF), epidermal growth factor (EGF) or interleukin-5 require proper glycosylation for their biological functions [26-29]. …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we have recently shown that N-glycosylation of the IL-6 receptor (IL-6R) is dispensable for its biological function, but rather influences limited proteolysis of the IL-6R by the metalloprotease ADAM17 [25]. In contrast, the receptors for C-X-C motif chemokine 12 (CXCL12), granulocyte-macrophage colony-stimulating factor (GM-CSF), epidermal growth factor (EGF) or interleukin-5 require proper glycosylation for their biological functions [26-29]. …”
Section: Introductionmentioning
confidence: 99%
“…Complete removal of the glycosylation of IL5 leads to a loss of ligand binding. More detailed studies of the contributions of the N-glycosylation sites on IL5 revealed that Asn 196 is required for ligand binding (9). Loss of the other three sites by mutation had no effect on IL5 affinity and biological activity (B-cell proliferation assay).…”
Section: Interleukinsmentioning
confidence: 99%
“…Mechanistic studies have revealed that IL5 induces biological activity through a two step process in which IL5 binds to the IL5 subunit leading to interaction with the preformed c subunit (9,10). The c then induces the signaling cascade within the target cell through activation of a kinase cascade by way of associated JAK kinases.…”
Section: Interleukinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Arginine-specific mono ADP-ribosylation in vitro of antimicrobial peptides by ADPribosylating toxins (Castagnini et al, 2012) Interleukin-5 receptor TOF Mutation of N-glycosylation sites to determine effect on function (Ishino et al, 2011) Interleukin-11 TOF (sinapinic), glycoprotein Introduction of O-glycans in the non-core region to investigate function (Yanaka et al, 2011) Lipoproteins…”
Section: Abbreviationsmentioning
confidence: 99%